Focused ultrasound as a stimulator of the nerve structures - GARVILOV, L. E. (Archives of Acoustics, 2015)
Pulsed focused ultrasound can stimulate the receptor and conductive nerve structures of man and animals, as well as neurons of the central nervous system of the invertebrates. The possibility of a wide practical use of this method in medicine and physiology is considered. For example, the stimulating ability of focused ultrasound is applied for neurological disease diagnosis, to study skin and tissue sensitivity of man, to diagnose hearing disorders and to introduce auditory information to the deaf with certain forms of hearing pathology. The effecting factors of focused ultrasound as a stimulus for nerve structures irritation are discussed.